تقييم الكفايات التدريسية لعضو الهيئة التدريسية في كلية التربية البدنية وعلوم الرياضة بجامعة كركوك - علي, وليد وعداهلل; حسين, امينة كريم; مجيد, سعدالله سعيد (Sulaimani Journal for Humanities, 2018)
The objective of the research is to evaluate the teaching competencies of a faculty member in the Faculty of Physical Education and Mathematical Sciences at the University of Kirkuk from their point of view. The research community included the teaching of the Faculty of Physical Education and Mathematical Sciences at the University of Kirkuk for the year 2016-2017. The sample of the research included (20) teaching methods. A scale of teaching competencies was used, which is codified on the Iraqi environment. (50) items distributed over (5) areas (objectives competencies, organizational competencies, implementation competencies, teaching methods competencies, assessment competencies), applied to the members of the research sample. After the questionnaire forms were processed by the appropriate statistical means. The most important conclusions are: 1 - Teachers of the Faculty of Physical Education and Sports Sciences at the University of Kirkuk have good teaching competencies in all areas 2 - The field of evaluation exceeds all areas of other teaching competencies.